CONTENT OF MACROAND MICROELEMENTS IN THE RATION OF CHILDREN NUTRITION - I. Y. Tarmayeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Nowadays there have been significant changes in the structure and quality of food in the territories of the various regions of the Russian Federation due to the dramatically changed economic and social conditions. Today there is no doubt that the major negative impact on the degree of negative action on the human body is a chronic shortage of micronutrients - vitamins, macro-and micronutrients and other biological compounds. Inadequate use of mineral elements with food in childhood has negative influence on the performance of physical development, promotes for developing of metabolic disturbances and chronic diseases. This is the base to expand the research for investigating of macro-and micronutrients composition of the children diets. Great impact on the health of the population has a natural-caused deficits or surpluses of the elements. First of all it is very importantfor Siberia and the Far East. With the use of modern laboratory studies there were conducted investigations of the content of macro-and micronutrients in the daily diet of organized pre-school children in Irkutsk. According to the analysis of laboratory studies, diets that given to children in Irkutsk in comparison with the diets of the children in Ulan-Ude are characterized by low content of most macro-and micronutrient elements and high levels of mercury (in1.9 time, p < 0,05) and iodine (in 4.0 time, p < 0,05). Comparison with normative values showed that the diet of Irkutsk preschoolers revealed deficiency of calcium, magnesium, iron, cobalt, and excess sodium and silicon. Investigation of the element balance in the pediatric population may have an important influence on the management decisions, could be the base in the activities of the preventive and clinical medicine and public health specialists as well as to serve as a methodological base for carrying out medical and environmental research in other regions of Russia.